The Relationship Of Students' Perceptions On Mathematics Lessons With Mathematics Learning Outcomes For Class V Students UPT SDN 11 Pangkajene, Sidrap Regency - Nurul Azizah Bahar; Sayidiman Sayidiman; Suarlin Suarlin (International Journal of Elementary School Teacher, 2022)
This research is a quantitative research with the type of correlational research which aims to determine 1) Description of students' perceptions of mathematics subjects, 2) Description of mathematics learning outcomes, 3) The relationship between students' perceptions of mathematics subjects and mathematics learning outcomes. The independent variable in this study is the students' perception of mathematics, while the dependent variable is the result of learning mathematics. The population in this study were all students of class V UPT SDN 11 Pangkajene Sidrap Regency as many as 3 classes with a total of 93 students, while the sample was 47 people with sampling using a systematic sampling technique. Data collection techniques in this research are questionnaires in the form of questionnaires and documentation. Data was collected from the distribution of questionnaires on student perceptions of mathematics subjects and documentation of UAS scores for even semester students for the 2020/2021 academic year. The data analysis technique used is descriptive analysis and inferential analysis using the product moment correlation test. The results of the research that have been carried out can be concluded that: (1) The description of students' perceptions of students' mathematics subjects is in the low category, it is obtained from the value of the average analysis results and the percentage of the results of filling out students' perception questionnaires on mathematics subjects, (2) The description of students' mathematics learning outcomes is in the good category, it is obtained from the value of the average analysis results and the percentage of students' mathematics learning outcomes, (3) Based on the results of inferential statistical analysis and decision making that refers to the criteria used to test the significant product moment correlation, it is obtained that the significance value does not meet the criteria or the significance value is greater than the alpha value, so the hypothesis in this study is rejected. Therefore, it can be concluded that there is no relationship between students' perceptions of mathematics subjects and the mathematics learning outcomes of fifth grade students of UPT SDN 11 Pangkajene, Sidrap Regency.